2018
DOI: 10.24874/jsscm.2018.12.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Smeared Concept as a General Methodology in Finite Element Modeling of Physical Fields and Mechanical Problems in Composite Media

Abstract: A generalization of the smeared concept for field problems, published in recent papers of the author and his collaborators, is presented in the paper. A composite smeared finite element CSFE is formulated. This generalization can serve as a theoretical background for further applications. A selected numerical example, related to convective-diffusive mass transport within a cancerous tissue, illustrates efficiency and accuracy of the smeared models. Further, a smeared methodology is extended to mechanical probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Fundamental equations for CSFE. Composite smeared finite element (CSFE) for modeling diffusion within a fiber network and the surrounding used here is in analogy with representation of mass transport within a capillary system and surrounding tissue [37][38][39][40][41] . Since axial diffusion within fibers can be neglected, we here only present formulation of the radial diffusion in the smeared concept.…”
Section: Diffusion Within Fibersmentioning
confidence: 99%
“…Fundamental equations for CSFE. Composite smeared finite element (CSFE) for modeling diffusion within a fiber network and the surrounding used here is in analogy with representation of mass transport within a capillary system and surrounding tissue [37][38][39][40][41] . Since axial diffusion within fibers can be neglected, we here only present formulation of the radial diffusion in the smeared concept.…”
Section: Diffusion Within Fibersmentioning
confidence: 99%
“…Perfusion and diffusion were simulated by using our developed Composite Smeared Finite Element (CSFE) method [ 15 , 16 ], which employs the concept of smeared physical fields, like fluid flow, molecule transport by convection and diffusion through capillary system and tissue, or capillary density. Fluid flow within capillaries is governed by the Hagen–Poiseuille law, while in tissue it is modeled according to the Darcy pressure–velocity relationship.…”
Section: Methodsmentioning
confidence: 99%
“…First, the 1D balance equations are necessary to be transformed into the corresponding continuum format. The derivations of the continuum transport tensor, for a general physical field, are given (Kojic, 2018) and can be expressed as…”
Section: Smeared Model For Field Problemsmentioning
confidence: 99%
“…Considering the complexity of computational modeling of physical fields, such as pressure distribution, concentration of various molecules, or field of electrical potential within a body, or even within an organ, it is desirable to have a computational methodology feasible for practical applications. In our previous research, we have introduced a smeared concept for mass transport in capillary system and tissue (Kojic et al, 2017a(Kojic et al, ,b, 2018(Kojic et al, , 2019Kojic, 2018;Milosevic et al, 2018a) and demonstrated its superiority with respect to traditional modeling methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation